Concepts of database management - Pratt, Philip J.; Adamski, Joseph J. (Singapore : Cengage Learning Asia Pte Ltd, 2012)
Completely updated to Microsoft Access 2013 standards, this text presents SQL in a database-neutral environment and covers topics such as: E-R diagrams, normalization, and database design. It also provides detailed coverage of the relational model (including QBE and SQL), normalization and views, database administration and management, and more.
Introduction to database management -- Relational model1: introduction, QBE, and relational algebra -- Retational model 2: SQL -- Relational model 3: advanced topics -- Database design 1: normalization -- Database design 2: design method -- DBMS functions -- Database administration -- Database management approaches.
"This edition is reprinted with license from Course Technology, a part of Cengage Learning, for sale in the Philippines only.:--Title page verso. 1st Philippine reprint 2012.
Includes index.
Keywords: DATABASE MANAGEMENT